Taṭbīq Ṭarīqah at-Targīb wa at-Tarhīb fī Taḥfiz al-Mufradāt al-‘Arabiyyah liṭullābi Ma‘ḥād ‘Ulumul Qur’ān Medan: The Application of Targhib and Tarhib Methods in Motivating Arabic Vocabulary Mastery among Students at the Ulumul Qur’an Institute, Medan - Ja’alna Salwinur Baeha; Zulfiana Herni (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2025)
Vocabulary mastery (mufradat) is the main key in improving the Arabic language skills of students in Islamic boarding schools. However, many students face obstacles in memorizing and using mufradat consistently in daily activities. This study aims to apply the targhib method (praise, rewards, and simple gifts) and tarhib (light, educational punishment) in motivating female students at the Ulumul Qur'an Islamic Boarding School in Medan to become more skilled at mastering and using Arabic mufradat. The study used a descriptive qualitative approach with data collection techniques through interviews, observation, documentation, and vocabulary mastery tests to assess the extent to which students are able to memorize and apply mufradat. The results showed that the balanced application of the targhib and tarhib methods can significantly improve mufradat mastery. Students are more active in memorizing, confident in using mufradat in activities such as giving speeches, reading books, and daily communication. Supporting factors for success include teacher competence, the religious environment of the Islamic boarding school, and students' internal motivation; while obstacles arise from limited study time and the inconsistency of the Islamic boarding school supervisor in the use of Arabic. This study confirms that the consistent implementation of targhib and tarhib is an effective strategy for improving Arabic vocabulary mastery and fostering learning motivation in Islamic boarding schools. Keywords: Arabic, Islamic Boarding School, Tarhib, Targhib, Vocabulary